A closer look - McCarthy, Mary, 1951 March 20- (Greenwillow Books, 2007)
Detailed collage illustrations accompanied by simple text present expanding views of some objects in nature, such as in this case, a ladybug, a hummingbird, a cardinal flower and a garden.